Analysis of the diffusion of scientific research on river basins (watersheds) in Brazil - Bordin, Deyver [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Putti, Fernando Ferrari [UNESP]; Gabriel, Camila Pires Cremasco [UNESP]; Góes, Bruno César [UNESP]; Satolo, Eduardo Guilherme [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2014)
River basins or watershed areas have suffered great impact due to deforestation and pollution, which in turn also comprises decrease in the volume of water in rivers involved. Current research overviews scientific literature related to the theme "Watershed", published between 2002 and 2012, and assess the scientific contribution. The research method consists of an exploratory bibliographical survey of Brazilian research on the above-mentioned subject retrieved from the database Web of Science (WoS). Data treatment was conducted through a bibliometric analysis to identify institutions with greater representation in publications and citations by region. The bibliometric analysis was performed with software developed in Delphi language and types of Microsoft Excel® software, Ucinet®, NetDraw® and ArcGIS® that enabled the development of graphical representations related to publications and citations by regions. When the analysis of bibliometric indicators was analyzed, the most productive institutions were mapped and the impact and visibility of their publications and relationships that occurred in collaboration between researchers from major institutions were evaluated. Research related to the theme "Watershed" has its largest production between physically close institutions. This fact shows the need for government action, through investments, for the integration of researchers from different regions to construct a national coverage for these networks. Finally, the Southeast Region of Brazil should be underscored due to its production of more than 50% of publications and citations out of the national total.

As bacias hidrográficas vêm sofrendo grande impacto devido ao desmatamento e a poluição, que consequentemente está apresentando redução no volume de água dos rios envolvidos nelas. O objetivo desta pesquisa é traçar um panorama da produção científica relacionado ao tema "Bacias Hidrográficas" no período entre 2002 e 2012, bem como mensurar a contribuição científica. Para tanto, este trabalho utilizou de como método de pesquisa o levantamento bibliográfico exploratório das pesquisas brasileiras no referido tema, a partir da base de dados Web of Science (WoS). A partir destes dados foi conduzido o tratamento dos dados por meio de uma análise bibliométrica a fim de identificar instituições com maior representatividade em publicações e citações por região. A análise bibliométrica foi realizada com um software desenvolvido em linguagem Delphi e dos tipos de software Microsoft Excel®, Ucinet®, NetDraw® e ArcGIS® que possibilitaram o desenvolvimento de representações gráficas que relacionaram as publicações e citações por regiões. Ao realizar a análise dos indicadores bibliométricos, mapeou-se as instituições mais produtivas, calculando o impacto e a visibilidade das publicações e os relacionamentos que ocorrem na colaboração entre pesquisadores das principais instituições. Conclui-se que a pesquisa relacionada ao tema "Bacias Hidrográficas" tem uma maior produção entre instituições fisicamente próximas, o que mostra a necessidade de uma atuação governamental, por meio de investimentos, facilitando assim, a integração de pesquisadores de diferentes regiões e possibilitando que essas redes tenham abrangência nacional. Por fim, merece destaque a região Sudeste do Brasil por possuir mais de 50% de publicações e citações do total nacional.
Análise da difusão das pesquisas científicas com bacias hidrográficas no Brasil
Keywords: Bibliometrics; Scientific collaboration; Water; Bibliometria; Colaboração científica; Água